Aplikasi Pupuk Organik terhadap Diversitas Arthropoda Akuatik serta Performa Tanaman Padi Hitam pada Ekosistem Sawah - Vira Kusuma Dewi; Tiara Febricyanti Putri Senjaya; Fitri Widiantini; Agus Susanto; Sri Hartati; Lindung Tri Puspasari; Rika Meliansyah (Soilrens, 2022)
The aquatic ecosystems in rice fields has macroorganisms such as aquatic arthropods which have an important function in the food web. The siam weed and neem cake can be utilized as organic fertilizer to support the productivity and biodiversity of the paddy field, This research aims to understand application of organic fertilizer on diversity of aquatic arthropods and black rice performance in the field ecosystem. The experiment was carried out in paddy field at Jatinangor from January to June 2020. The method used was an experimental method with a Randomized Complete Block Design consisted of five treatments (neem cake, siam weed compost, cow manure, synthetic fertilizer and control) with six replications. The result showed that the abundances of aquatic arthropods have tendency to be higher in neem cake at 1104 individuals and siam weed compost treatments at 905 individuals compared to the cow manure, NPK and control. Furthermore, the diversity index of the aquatic arthropods in all treatments were categorized as moderate with details as follow neem cake (H’=1,726), cow manure (H’=1,450); synthetic fertilizer (H’=1,458); siam weed compost (H’=1,450) and control (H’=1,502). In addition, the evenness index (E) of aquatic arthropods was higher in neem cake treatment (E=0,623) compared to other treatments. Whereas, the dominance index (C) and richness index (R) in all treatments showed no dominant species and it classified as low category. The results also showed that the siam weed compost were not significantly different with all treaments except NPK (synthetic fertilizer) in plant hight, tiller number and SPAD value.